2019
DOI: 10.1016/j.promfg.2020.01.313
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Passive Chip Components Placement with Self-Alignment Effect for Advanced Surface Mounting Technology

Abstract: Surface mount technology (SMT) is an enhanced method in electronic packaging in which electronic components are placed directly on soldered printing circuit board (PCB) and are permanently attached on PCB with the aim of reflow soldering process. During reflow process, once deposited solder pastes start melting, electronic components move in a direction that achieve their highest symmetry. This motion is known as self-alignment since can correct potential mounting misalignment. In this study, two noticeable ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In general, the SMT process contains three operations: the stencil printing process (SPP), pick-and-place (chip mounting) process, and reflow soldering [1][2][3]. First, solder paste is printed onto the surface of a PCB by a stencil printer.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the SMT process contains three operations: the stencil printing process (SPP), pick-and-place (chip mounting) process, and reflow soldering [1][2][3]. First, solder paste is printed onto the surface of a PCB by a stencil printer.…”
Section: Introductionmentioning
confidence: 99%
“…Hidden Markov models are also widely used in ECG segmentation because they are powerful tools for considering the temporal dependency among the waveforms [13][14][15]. The majority of the studies on machine learning-based methods have utilized sparse signal processing to represent an approximation of the nonlinear ECG signal using sparsity constraints [16][17][18][19][20][21]. Some studies have also applied deep learning techniques to detect the ECG waveforms considering its high performance in various classification tasks [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that placing components on the pastes had better performances than placing them on the pad. Recently, non-linear programming models were employed in the P&P process to identify the optimal placement locations based on the predicted components movement information [10].…”
mentioning
confidence: 99%